Practical instrumental analysis : methods, quality assurance and laboratory management - Petrozzi, Sergio (Wiley-VCH, 2013)
The essential practical guide for analytical chemists working in industry, covering all the common methods used in industrial analytical labs. The author has a background in industry as well as extensive experience in teaching this topic, so he knows the field from the inside and can explain the contents in an easily understandable way. The first part of the book introduces the basic theoretical aspects of instrumental analysis, while the second consists of experiments that are structured as projects to be carried out by a team, thus guiding the reader into thinking like an industrial analytical chemist. As a result, readers learn how to work efficiently, safely and accurately in an industrial setting.- Resumé vydavatele
Keywords: instrumentální analýza; analytická chemie; instrumental analysis; analytical chemistry; elektronické knihy; příručky; electronic books; handbooks and manuals